The electrical and mechanical properties of Au-V and Au- V2 O5 thin films for wear-resistant RF MEMS switches - Thirumalesh Bannuru (2018)
To explore alternatives to the use of pure Au in Ohmic contact RF microelectromechanical switches, we have measured changes in the electrical resistivity and nanoindentation hardness of a series of sputter deposited Au-V and Au- V2 O5 thin films. Increasing V content in the Au-V alloys increases resistivity and hardness, which is consistent with solid solution strengthening. In the Au- V2 O5 films, the increase in resistivity is greatly reduced and the hardness is further increased as expected for dispersion strengthening with V2 O5 particles. These two phenomena are explained in terms of solute and particle effects on electron scattering and bowing of dislocations, respectively. © 2008 American Institute of Physics.